Apricardia manuelae n. sp. in the lower Turonian of northeastern Matese (south Apennines), Italy - Michele Mainelli (Revista Mexicana de Ciencias Geológicas)
A new species (Apricardia manuelae) in described from the carbonate neritic facies of the lower Turonian in the northeastern Mate Massif, located at the southern part of the Apennines of Italy… in order to continue, download the full paper in PDF.